Haitian Variant Vibrio cholerae O1 Strains Manifest Higher Virulence in Animal Models - Ghosh, Priyanka; Sinha, Ritam; Samanta, Prosenjit; Saha, Dhira Rani; Koley, Hemanta; Dutta, Shanta; Okamoto, Keinosuke; Ghosh, Amit; Ramamurthy, T.; Mukhopadhyay, Asish K. (Frontiers in Microbiology, 2019)
Vibrio cholerae causes fatal diarrhoeal disease cholera in humans due to consumption of contaminated water and food. To instigate the disease, the bacterium must evade the host intestinal innate immune system; penetrate the mucus layer of the small intestine, adhere and multiply on the surface of microvilli and produce toxin(s) through the action of virulence associated genes. V. cholerae O1 that has caused a major cholera outbreak in Haiti contained several unique genetic signatures. These novel traits are used to differentiate them from the canonical El Tor strains. Several studies reported the spread of these Haitian variant strains in different parts of the world including Asia and Africa, but there is a paucity of information on the clinical consequence of these genetic changes. To understand the impact of these changes, we undertook a study involving mice and rabbit models to evaluate the pathogenesis. The colonization ability of Haitian variant strain in comparison to canonical El Tor strain was found to be significantly more in both suckling mice and rabbit model. Adult mice also displayed the same results. Besides that, infection patterns of Haitian variant strains showed a completely different picture. Increased mucosal damaging, colonization and inflammatory changes were observed through haematoxylin-eosin staining and transmission electron microscopy. Fluid accumulation ability was also significantly higher in rabbit model. Our study indicated that these virulence features of the Haitian variant strain may have some association with the severe clinical outcome of the cholera patients in different parts of the world.